Burden of Unintentional Childhood Injuries in Pre-School Children (2-6yrs) and Knowledge of Primary Caregivers on Early Management: A Descriptive Observational Study in Urban Slums of Bhubaneswar, Odisha - Asutosh Pradhan; Sonali Kar; Swarnalata Das; Krishna Mishra (Journal of Public Health International, 2024)
Background Injuries, particularly unintentional ones, are a neglected public health concern and are preventable or avoidable. Children in urban slums are especially vulnerable due to hazardous living conditions, inadequate supervision, and lack of safe sojourns or play areas. Since these injuries result in seeming spontaneous recovery, appropriate care being initiated by the primary care giver is questionable. Objective To assess the burden of unintentional injuries of unintentional injuries in pre-school going children aged 2-6 years in urban slums of Bhubaneswar, Odisha. To compare the knowledge of the 1st level care post-injury among the primary care givers against standardized prescribed care. Methods A cross-sectional descriptive observational study was conducted for over 2 years in urban slums under the Bhubaneswar Municipal Corporation (BMC), the capital city of Odisha. A total of 285 children aged 2-6 years, whose mothers consented to participate, were included in the study. Data regarding the type of injury and its management, as well as, associated socio-demographic factors, were collected using a pre-designed, pre-tested questionnaire. Descriptive statistics was used to derive the burden of unintentional injuries in children. The knowledge of the 1st level of care to be given after the common injuries was assessed among all the primary caregivers to detect the treatment and care gap. Results The majority of primary respondents were mothers aged 21-30 years (82.1%), The frequency of an episode of unintentional injury (occurrence in last 3 months) in the study population was found to be 58%. The most common type of injury reported was skin lacerations or tears, common site being in the upper and lower limbs. Males were more affected as compared to females (54.64 %) The reporting of unintentional injuries among the children was found to have significant association with the occupation of the father. Fathers who were unemployed or working as unskilled labor, their child’s probability of reporting an unintentional injury was found to be high, with p value coming to be statistically significant. Conclusion The study highlights the complex interplay of sociodemographic factors influencing unintentional injuries among children in urban slums and the need to create awareness among the primary caregivers, about the immediate management, so that chronic complications may be averted. It is difficult to avert injury as this age group is agile and nowadays supervision is challenging. Still, the knowledge of management would not just empower the caregiver, but also the growing child, who can attend to their younger siblings or themselves, whenever they get injured next. Further research with larger sample sizes is warranted to validate these findings and develop effective prevention strategies.
Keywords: Unintentional injuries